On the interaction between own revenues and intergovernmental transfers : Evidence from Argentinean local governments - Puig, Jorge Pablo (2021)
In this paper we study the interaction between intergovernmental transfers on the level and the structure of local own revenues. Based on a sample for Argentina’s local governments, findings indicate that transfers facilitate local revenues collection. This “crowding-in” effect is more pronounced in urban local governments, with higher population density, poverty and demand for public services. In addition, transfers bias own revenues composition towards less distortionary taxation (i.e., property tax). Interestingly, this bias is stronger for local governments with higher share of indivisible public goods (that are less likely to be finance according to the “benefit principle”). Results are robust to a battery of different estimation methods, and can be rationalized with theory from public finance and political economy as well. As a whole findings might have important policy implications on local governments public finance.